Impact of lithium chlorate salts on structural and electrical properties of natural polymer electrolytes for all solid state lithium polymer batteries. (January 2019) - Perumal, P.; Selvasekarapandian, S.; Abhilash, K.P.; Sivaraj, P.; Hemalatha, R.; Selvin, P. Christopher
Abstract: Two different solid biopolymer electrolytes (SBEs), based on natural polysaccharide pectin were prepared via solution casting technique. The structural and electrical properties of the prepared electrolytes were studied by XRD and AC impedance characterization techniques. The XRD results reveal that, the 50 (m.m.%) LiCl incorporation greatly enriched the amorphous region of the pectin host polymer. The 50 (m.m.%) pectin: 50 (m.m.%) LiCl possessed an excellent ionic conductivity of 1.96 × 10 −3 Scm −1, which is superior to the LiClO4 incorporated electrolyte showing an ionic conductivity of 5.38 × 10 −5 Scm −1 for the composition of 60 (m.m.%) pectin: 40 (m.m.%) LiClO4. The pectin-based biopolymer exhibits better mechanical stability and stable cycling performance with minimum charge transfer resistance in different full cell configurations. Highlights: Study on impact of lithium chlorates salts on structural and electrical properties of biopolymer pectin based electrolytes. Enhancement in ionic conductivity, electrochemical stability and cyclability of bio-polymer by the incorporation of salts. Lower value of charge transfer resistance on the assembled solid state battery.